2017
DOI: 10.18632/oncotarget.18855
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in patients with candidiasis: a nationwide population-based cohort study

Abstract: BackgroundCandidiasis and certain types of cancer are related to immunocompromised status. This study aimed to evaluate whether Candida infection (CI) is associated with subsequent cancer risk in Taiwan.MethodsData from the National Health Insurance system of Taiwan were used to evaluate the association between CI and cancer risk. The CI cohort comprised 34,829 patients. Each patient was randomly frequency matched with one person from the general population without CI on the basis of age, sex, year of index da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…Moreover, a negative correlation between Candida and Campylobacter in HIV-infected patients was also reported in this study, whereas in healthy subjects, no correlation between Candida and bacterial species was found [47]. Candida species is a well-known oral fungal pathogen, and studies have shown that infection with this species can significantly increase overall and some individual cancer risks, for example, head and neck, pancreatic, skin, and thyroid cancers [48]. A study in colorectal cancer patients has revealed dysbiosis in mycobiome characterised by change in fungal composition and ecology, which suggests the important role of gut mycobiome also in CRC [49].…”
Section: Role Of Microbiota In Cancersupporting
confidence: 54%
“…Moreover, a negative correlation between Candida and Campylobacter in HIV-infected patients was also reported in this study, whereas in healthy subjects, no correlation between Candida and bacterial species was found [47]. Candida species is a well-known oral fungal pathogen, and studies have shown that infection with this species can significantly increase overall and some individual cancer risks, for example, head and neck, pancreatic, skin, and thyroid cancers [48]. A study in colorectal cancer patients has revealed dysbiosis in mycobiome characterised by change in fungal composition and ecology, which suggests the important role of gut mycobiome also in CRC [49].…”
Section: Role Of Microbiota In Cancersupporting
confidence: 54%
“…For example, a prospective cohort study conducted in Sweden showed that Candida infection in the oral cavity was associated with development of PC [55]. Similarly, another population-based cohort study in Taiwan showed that risk of PC was significantly higher among Candida -infected individuals [56]. However, the relationships between fungal infections and PC require further study.…”
Section: Roles Of Microbiomes In Development Of Pcmentioning
confidence: 99%
“…Studies have suggested that Candida albicans are associated with number of opportunistic infections in immunocompromised patients like in HIV patients, cancer patients and diabetic patients etc. [3].…”
Section: Introductionmentioning
confidence: 99%